Food ingestion, consumption and selectivity of pompano, Trachinotus ovatus (Linnaeus 1758) under different rotifer densities. (24th March 2014) - Ma, Zhenhua; Guo, Huayang; Zhang, Dianchang; Hu, Chaoqun; Jiang, Shigui
Abstract The growth, survival, food selection and consumption of pompano larvae under different rotifer densities as well as their colour preference during the rotifer feeding stage were examined in this study. Growth and survival of fish larvae were not significantly affected when rotifer density was between 10 and 20 mL−1. Fish larvae grew slower at 1 and 40 rotifers mL−1 than at 10 and 20 rotifers mL−1, and higher fish survival was achieved when fish larvae were exposed to 10 and 20 rotifers mL−1. The rotifer density of 1 mL−1 not only reduced food ingestion during the early stage, but also delayed diet switch from rotifer to copepod nauplii. On 5 days post hatching (DPH), larval pompano ingested more rotifers in dark‐coloured tanks and ingested more rotifers when prey colour was green. Based on the results obtained in the present study, the culture of larval pompano larvae is recommended using dark wall tanks with a feeding density of 10–20 rotifers mL−1 during the initial feeding stage. This study proposes a management protocol to use appropriate type and quantity of live food to feed pompano larvae in a hatchery rearing condition, which could be applicable to the culture of fish larvae in other marine fish species.